Perancangan Smart Meter Berbasis IoT Untuk Aplikasi Pembangkit Listrik Tenaga Surya Microgrid: Proposal Penelitian - Hidayat, Taufal; Firmansyah, Dwiki (Jurnal Teknik Elektro, 2019)
Photovoltaic (PV) Microgrid is one solution to meet the electricity demand in remote areas and is difficult to reach by the PLN. This type of PLTS has advantages over the types of off grid Photovoltaic, especially in terms of installation and financing costs. One of the challenges in the application of PLTS microgrid is the process of monitoring power and performance of PLTS. Smart meters are one of the most potential solutions to be applied to monitor solar power plants. In this study, a prototype of a smart meter system from PLTS will be designed using the Arduino micro controller as a data processing module, ESP12 module as a communication module and ACS712 sensor as a current and voltage sensor.